Substance Use Treatment and Reentry (STAR) Program Final Evaluation Report - Hunter, Sarah B. (RAND Corporation, 2014)
The Substance Abuse and Mental Health Services Administration (SAMHSA), Center for Substance Abuse Treatment (CSAT), awarded grants to community organizations to expand and/or enhance reentry services to young offenders with substance use disorders on release. This report evaluates the Substance Use Treatment and Reentry (STAR) Program of Homeboy Industries, Inc., in collaboration with Behavioral Health Services, Inc., and the RAND Corporation.